Laboratorium analizy filmu Z prof. Sewerynem Kuśmierczykiem rozmawia Robert Birkholc - Birkholc, Robert; Kuśmierczyk, Seweryn (Załącznik Kulturoznawczy, 2018)
Interview with professor Seweryn Kuśmierczyk on his research and didactic work, especially on the morphological-anthropological method of film analysis that he invented and elaborated as an academic teacher.